STABILITY ANALYSIS OF SLOPE ON TRANS SULAWESI ROAD, PONTOLO VILLAGE, MANANGGU SUB-DISTRICT, BOALEMO DISTRICT, GORONTALO PROVINCE - Indriani Indriani; Sri Maryati; Ronald Hutagalung (USN Kolaka, 2022)
The research location is in Pontolo Village, Mananggu Sub-district, Boalemo District, Gorontalo Province. The research location has rock slopes with a discontinuity area in the form of fractures in the rock body, which is a factor causing landslides. The research aims to determine geological conditions, rock mass quality, types of potential landslides, and recommendations for slope stability. The methods used are direct field observation, Scanline Mapping, Rock mass Rating (RMR), kinematics analysis, and Slope Mass Rating (SMR). The results of the geomorphological research of the research area are units of lava flow plains and units of intrusive hills. The lithology of the research area is in the form of granodiorite units and porphyry dacite units, while the geological structure is in the form of joints. Scanline mapping is carried out in 4 segments: segment 1, segment 2, segment 3 and segment 4. The rock mass class consists of 2 classes, a good class and a fair class. Types of landslides consist of wedge sliding and toppling sliding. SMR consists of 2 classes, stable and unstable, the results of observations that unstable slopes need to be handled in slope reinforcement.